2007
DOI: 10.1016/j.pbb.2007.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Chronic nicotine administration improves attention while nicotine withdrawal induces performance deficits in the 5-choice serial reaction time task in rats

Abstract: Nicotine appears to enhance attention, while nicotine withdrawal leads to attentional deficits in humans that are ameliorated with nicotine administration. However, there has been much debate as to whether nicotine improves performance under baseline conditions, or only ameliorates attentional deficits. Thus, we studied the effects of acute and chronic nicotine administration and nicotine withdrawal on attentional performance in the 5-choice serial reaction time task (5-CSRTT) in Wistar and Sprague Dawley (SD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 50 publications
7
83
0
Order By: Relevance
“…restoration) of inhibitory control during No-go trials in the final days of drug treatment, a pattern most likely due to the development of tolerance to the effects of the drug. Similar findings have been reported for anticipatory responding in the 5CSRTT in animals examined at the end of a comparable nicotine treatment regime (Semenova et al 2007;Shoaib and Bizarro 2005) and in those chronically self-administering cocaine (Winstanley et al 2009). Indeed, the development of tolerance to nicotine during chronic or repeated drug exposure has been observed across a range of behaviours and physiological responses both in animals Harrison et al 2001) and smokers (Perkins 2002).…”
Section: Effects Of Chronic Nicotinesupporting
confidence: 80%
See 1 more Smart Citation
“…restoration) of inhibitory control during No-go trials in the final days of drug treatment, a pattern most likely due to the development of tolerance to the effects of the drug. Similar findings have been reported for anticipatory responding in the 5CSRTT in animals examined at the end of a comparable nicotine treatment regime (Semenova et al 2007;Shoaib and Bizarro 2005) and in those chronically self-administering cocaine (Winstanley et al 2009). Indeed, the development of tolerance to nicotine during chronic or repeated drug exposure has been observed across a range of behaviours and physiological responses both in animals Harrison et al 2001) and smokers (Perkins 2002).…”
Section: Effects Of Chronic Nicotinesupporting
confidence: 80%
“…Blondel et al 1999;Semenova et al 2007) but also supports the increase in disinhibition and impulsive choice following chronic treatment/self-administration with other psychostimulants such as cocaine and methamphetamine (e.g. Jentsch et al 2002;Richards et al 1999;Winstanley et al 2009).…”
Section: Effects Of Chronic Nicotinementioning
confidence: 56%
“…Nevertheless, we used Wistar strain rats because they are easily handled and show relatively high impulsive-like action (Broersen and Uylings, 1999;Semenova et al, 2007). Also, if the number of holes had been decreased, the duration of training may have been shortened further because a previous report using 2-lever choice task showed that rats moved onto experimental periods only with 24 sessions of training (Evenden, 1999b).…”
Section: Discussionmentioning
confidence: 99%
“…Each trial was initiated automatically, not by a panel push. In this way, the rat was required to use more attentional resources (Semenova et al, 2007) because it could not proceed with the task at its own pace. Furthermore, the stimulus duration was 1 s instead of 0.5 s, because we used Wistar rats, which show poor attention and high impulsive-like action compared to Lister hooded rats (Broersen and Uylings, 1999;Ohmura et al, 2009).…”
Section: -Csrtt Test Proceduresmentioning
confidence: 99%
“…The patch or an osmotic minipump implant might implement a more effective drug administration. However, one group has already demonstrated that the continuous infusion of a high dose of nicotine using an osmotic minipump evoked impulsive behavior in rats, although the effects gradually disappeared over a period of days (51,100). Further studies using osmotic minipumps with smaller doses of nicotine are necessary to confirm this result.…”
Section: The Route Of Nicotine Administrationmentioning
confidence: 99%